O.M. Poe papers - Poe, O. M. (Orlando Metcalfe), 1832-1895.
Correspondence, diaries, writings, speeches, reports, orders, notebooks, family papers, biographical material, newspaper clippings, maps, drawings, memorabilia, and other papers relating primarily to Poe's military service as an engineer during the Civil War and Reconstruction and his friendship with Gen. William T. Sherman whom he served as aide-de-camp from 1873 to 1884. Includes material on his stint as chief engineer with the Army of the Ohio, campaigns with Sherman in Georgia, South Carolina, and Tennessee, and other engagements in the western theater of the war. Postwar engineering projects documented include the Spectacle Reef lighthouse on Lake Huron, the Hennepin Canal (the portion known then as the Illinois-Mississippi Canal), and the canal at Saulte Ste. Marie, Mich. Includes over one hundred letters between Poe and Sherman. Other correspondents include Hartman Bache, Zachariah Chandler, Jacob Merritt Howard, W.F. Raynolds, Charles N. Turnbull, and R.S. Williamson.
Library of Congress Geography and Map Division.
Library of Congress Prints and Photographs Division.
Library of Congress Serial and Government Publications Division.
Library of Congress General Collections.
U.S Army officer and engineer.
Collection material in English.
Keywords: Bache, Hartman, -- 1797-1872 -- Correspondence; Chandler, Zachariah, -- 1813-1879 -- Correspondence; Howard, Jacob Merritt, -- 1805-1871 -- Correspondence; Raynolds, W. F. -- 1820-1894 -- Correspondence; Sherman, William T. -- 1820-1891.; Sherman, William T. -- 1820-1891 -- Correspondence; Turnbull, Charles N., -- 1832-1874 -- Correspondence; Williamson, R. S. -- 1824-1882 -- Correspondence; United States. -- Army -- Officers; United States. -- Army of the Ohio; Canals -- Great Lakes (North America); Canals -- Illinois; Canals -- Michigan; Lighthouses -- Great Lakes (North America); Military engineering; Reconstruction (U.S. history, 1865-1877); Georgia -- History -- Civil War, 1861-1865.; Huron, Lake (Mich. and Ont.); Hennepin Canal (Ill.); Sault Sainte Marie Canal (Mich.); South Carolina -- History -- Civil War, 1861-1865.; Spectacle Reef (Mich.); Tennessee -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Campaigns; United States -- History -- Civil War, 1861-1865 -- Engineering and construction; Army officers; Engineers